The Role of Wearable Technology in Enhancing Public Health and Lifestyle Improvement in South Korea - Mira Sapriyawati; Shannaz Mutiara Deniar; Gonda Yumitro; Gautam Kumar Jha (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Wearable technology is an emerging innovation in the digital era that refers to electronic sensor devices commonly used in daily life to support health monitoring and lifestyle management. This study examines the role of wearable technology in enhancing public health and promoting a healthier lifestyle in South Korean society. Using a qualitative descriptive approach, this research analyzes secondary data from previous studies and user experiences with wearable devices, including smartwatches, smart bands, and fitness trackers. The findings show that wearable technology significantly increases health awareness through continuous monitoring and feedback, particularly in physical activity, sleep quality, and stress management. This study contributes to existing literature by conceptualizing wearable technology not merely as an individual health tool, but as a strategic digital health instrument embedded within South Korea’s technological infrastructure and public health ecosystem. Overall, wearable technology demonstrates strong potential in supporting preventive healthcare and sustainable public well-being.